A Stackelberg Game Theory Model for Integrated Community Energy Storage Systems - Sobhan Dorahaki; S. M. Muyeen; Nima Amjady (IEEE Access)
The rise of distributed energy resources (DERs) in the energy landscape underscores the pivotal role of prosumers in the ongoing energy transition. With the significant investment required for individual energy storage (IES), community energy storage (CES) emerges as a key facilitator, enabling the smooth incorporation of renewable energy sources and strengthening grid flexibility. This paper explores the dynamic interplay between CES owners, who serve as key economic actors in local energy communities, and prosumers within these communities through a Stackelberg game framework. A bi-level optimization framework aimed at empowering CES systems is introduced to address the proposed Stackelberg game framework. At the upper level of this framework, the goal is to maximize the profit of the CES system while the flexibility limits of the upstream electricity grid and other constraints are addressed. On the other hand, individual prosumers at the lower level optimize their actions to minimize billing costs and enhance comfort in alignment with their preferences. The bi-level optimization problem is reformulated into a linear single-level optimization problem using the Karush-Kuhn-Tucker (KKT) approach. The results indicate that implementing flexibility constraints can effectively smooth energy exchanges with the upstream grid. However, the distribution system operator must account for the potential reduction in the CES system’s operational profit to incentivize the CES owner to participate in the flexibility enhancement program.